Bronchogenic cyst presenting congenital cervical cutaneous contracture - Masafumi Kamata; Ikkei Tamada; Marie Aoki (Elsevier, 2020)
Bronchogenic cysts are rare congenital malformations resulting from abnormal budding of the tracheobronchial tree. We describe herein a rare case of cervical subcutaneous bronchogenic cyst found during surgery for a skin contracture in the midline of the neck, which was present from birth. Although such hypertrophic, scar-like findings are extremely rare in subcutaneous bronchogenic cysts, they should be recognized as a possible phenotype. Included is a review of previous reports.